(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the issues of social adaptation and ensuring the mental health of women living in military families in the context of globalization. During the study, psychological factors, stress situations, and emotional stability issues that arise in the process of women’s adaptation to the social environment were studied. The importance of modern psychological approaches, including psychological counseling, training, and a social support system, was also analyzed. The results of the study show that a healthy family environment and psychological support play an important role in strengthening women’s mental health.